Analysis of key trends and ways to improve the marketing activities of domestic manufacturers of municipal equipment - I. Yu. Okolnishnikova; E. V. Sumarokova; E. V. Krasnov (Вестник университета)
The results of the marketing analysis of the market of special equipment for housing and communal services of Russia are presented. Market trends have been analysed, the sales dynamics of municipal machinery have been characterised and segments of the product portfolio of domestic manufacturers have been identified. The article analyzes the features of the development of two key product segments - the segment of snowplows and snow loaders, as well as the segment of garbage trucks. It is proved that they have a high market potential and objective prerequisites for import substitution, but they need to improve marketing support. The authors proposed and justified a set of measures to improve marketing activities, including development of financial instruments to support customers, expansion of the product line, improvement of distribution strategies, optimisation of call centers and the development of exports using state support tools.